As práticas informais e o aprendizado não-formal na oficina de música do projeto PIBID/ESMU/UEMG - Fernando Macedo Rodrigues (2017)
This research aimed to discuss the non-formal learning processes and the informal practices of musical learning in the music workshop of the PIBID/UEMG PIBID - Institutional Scholarship Program of Teaching Initiation. UEMG - State University of Minas Gerais Brazil. project in a public high school in Belo Horizonte. It was investigated the applicability and adaptation of these approaches in a Brazilian school context and the possibility of these being used as instruments to stimulate the processes of practice, teaching and musical learning. The music workshop was held on a weekly basis with three hours a day, divided into three parts: group dynamics, instrument class and group musical practice. Non-formal learning (D'AMORE, 2012) was prominent in the first two moments, and informal practices (GREEN, 2008) were centralized in the third moment. The characteristics of collective education (CRUVINEL, 2005; TOURINHO, 2007), the collaborative approach (RENSHAW, 2005) and peer learning (GREEN, 2001, 2008) were observed throughout the course of the workshop. Using qualitative research methodology (MERRIAN, 2003) and data collection from observations, questionnaires, interviews, and video recordings during the workshop's musical practices, it was possible to raise the opinions and conceptions of the participants - five university students (Scholars) and twenty students from the school - about the activities developed during the 2014 school year. Technology and electronic devices, such as computers and cell phones, have been highlighted by their use, both before and during the workshop, in the search for various musical information and/or how to play a desired song or excerpt, with emphasis on Cifraclub and Youtube websites as important references. Through the activities there was a sharing of strategies, information and learning among scholars, among students, and between scholars and students. In relation to the Scholars, a space was provided, through the structure offered by the project and public school, for the exercise of teaching through the planning, execution and reflection of developed musical activities. We also observed that there was an increase in the interaction and motivation of students interested in various musical subjects, including practice and music theory. As a result, we can highlight that: the project facilitated the exercise of collaborative learning among the participants; the research proved the feasibility and the possibility of a proximity between the non-formal and informal approaches and provided an update of the characteristics of the informal practices (GREEN, 2008) from the use of several technological resources.